2021
DOI: 10.1016/j.annonc.2021.05.801
|View full text |Cite
|
Sign up to set email alerts
|

Primary results from IMpassion131, a double-blind, placebo-controlled, randomised phase III trial of first-line paclitaxel with or without atezolizumab for unresectable locally advanced/metastatic triple-negative breast cancer

Abstract: Background: In the phase III IMpassion130 trial, combining atezolizumab with first-line nanoparticle albumin-boundpaclitaxel for advanced triple-negative breast cancer (aTNBC) showed a statistically significant progression-free survival (PFS) benefit in the intention-to-treat (ITT) and programmed death-ligand 1 (PD-L1)-positive populations, and a clinically meaningful overall survival (OS) effect in PD-L1-positive aTNBC. The phase III KEYNOTE-355 trial adding pembrolizumab to chemotherapy for aTNBC showed simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
321
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(335 citation statements)
references
References 14 publications
6
321
0
8
Order By: Relevance
“…In the IMpassion130 trial, the median OS was 21.3 months in the atezolizumab-nab-paclitaxel group and 17.6 months in the placebo-nab-paclitaxel group [ 6 ]. Another phase III clinical trial, IMpassion131, documented a median OS of about 20 months in patients receiving paclitaxel with or without aztezolizumab [ 28 ]. This might be because these clinical trials did not include TNBC patients who might have experienced worse treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the IMpassion130 trial, the median OS was 21.3 months in the atezolizumab-nab-paclitaxel group and 17.6 months in the placebo-nab-paclitaxel group [ 6 ]. Another phase III clinical trial, IMpassion131, documented a median OS of about 20 months in patients receiving paclitaxel with or without aztezolizumab [ 28 ]. This might be because these clinical trials did not include TNBC patients who might have experienced worse treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in PD-L1-positive patients, OS increased from 18 to 25 months (HR 0.71; 95% CI 0.54-0.94). Surprisingly, the recently presented IMpassion131 trial combining atezolizumab with conventional paclitaxel in advanced TNBC did not improve PFS or OS compared with placebo + paclitaxel [72]. Of 651 randomized patients, 45% had PD-L1-positive aTNBC.…”
Section: Icpi In Advanced Breast Cancermentioning
confidence: 93%
“…In the PD-L1-positive population, atezolizumab and paclitaxel were associated with a more favorable unconfirmed overall response rate (63% vs. 55% for placebo-paclitaxel) and a longer median duration of response (7.2 and 5.5 months, respectively). Possible reasons for this apparent contrast with the benefit observed in IMpassion130 require further investigation, although several hypotheses (e.g., different taxanes and the role of steroids or imbalances in prognostic features or random results in a relatively small study) are under discussion [72,73].…”
Section: Icpi In Advanced Breast Cancermentioning
confidence: 99%
“…Similarly, Atezolizumab also targets PD-L1, and it has been approved to treat metastatic TNBC in combination with paclitaxel [107]. However, a recent study indicated that combination treatment of paclitaxel and atezolizumab did not elicit an improved outcome in TNBC patients compared to the placebo group [237]. Yet another study showed that the combination treatment with paclitaxel and atezolizumab resulted in an improved overall survival rate in TNBC patients with enriched PD-L1 compared to the placebo group [238].…”
Section: Immunotherapymentioning
confidence: 99%